EKSISTENSI TAFSIR MODERN : STUDI ANALISIS PERKEMBANGAN SUMBER, CORAK DAN METODE TAFSIR MODERN - Abdul Muhaimin Mas’ulil Munawaroh (Ibn Abbas : Jurnal Ilmu Alquran dan Tafsir, 2019)
The existence of the Qur'an which is always relevant throughout the time (sha> lihun li kulli zama>n) directly provides space for the interpreters to interpret the Qur'an in accordance with the demands of the times. Modern interpretation is the product of contemporary interpreters who have new things in accordance with the context of the present era. If the classical interpretation has a source, style and method of interpretation, the modern interpretation also has the same thing as the classical interpretation. The development of modern interpretation sources begins by using the method of al-iqtira> ni (a combination of bi al-manqu>l and bi al-ma’thu>r). The development of the Modern interpretive method begins with the Islamic method> li then singular thematic interpretations (al-Maudhu> 'i al-Aha>d), prular thematic methods (al-Maudhu>' i al-Ja>mi ') and interpretations that discuss just one sentence by gathering all the verses using the sentence or derivation and the root of the sentence, then interpreting them one by one and expressing the theorem and its use in the Qur'an.